2019
DOI: 10.1186/s12906-019-2569-6
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide induces mitochondria-mediated apoptosis in human gastric adenocarcinoma BGC-823 cells

Abstract: Background: Costunolide, a sesquiterpene lactone extracted from Radix Aucklandiae, has the activity against multiple cancers. However, the effect of costunolide on gastric cancer (GC) have remained to be ambiguous. In this study, we investigated the underlying mechanisms of apoptosis induced by costunolide in human gastric adenocarcinoma BGC-823 cells in vitro and in vivo. Methods: The viability of BGC-823 cells was detected by MTT assay. The apoptosis and mitochondrial membrane potential (ΔΨm) of BGC-823 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
(38 reference statements)
2
14
0
Order By: Relevance
“…Costunolide is a sesquiterpene lactone (24), which has been reported to exert antiproliferative effects against a wide range of cancer cells, including gastric cancer (25), leukemia (26), colorectal cancer (27) and lung cancer (16). The results of the present study demonstrated that costunolide inhibited the proliferation of H1299 NSCLC cells, with an IC 50 value of 23.93±1.67 µM.…”
Section: Discussionsupporting
confidence: 48%
“…Costunolide is a sesquiterpene lactone (24), which has been reported to exert antiproliferative effects against a wide range of cancer cells, including gastric cancer (25), leukemia (26), colorectal cancer (27) and lung cancer (16). The results of the present study demonstrated that costunolide inhibited the proliferation of H1299 NSCLC cells, with an IC 50 value of 23.93±1.67 µM.…”
Section: Discussionsupporting
confidence: 48%
“…Costunolide, a sesquiterpene lactone exist in the genus Compositae and Magnoiaceae (Park et al, 2001), was also detected in MsHE. It has been reported to have many physiological activities, such as antioxidant, anti‐inflammation, anti‐allergic, antimicrobial and can induce apoptosis of gastric adenocarcinoma (Yan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that CTD suppressed cancer cell proliferation by altering cell cycle progression through the regulation of cyclins and cyclin-dependent kinases (CDK) [ 33 , 36 , 37 ]. Additional literature has also reported that CTD can induce apoptosis via activated p53 or mitochondrial damage through increased production of reactive oxygen species (ROS) in colon, gastric and lung cancers [ 21 , 37 , 38 , 39 ]. These observations suggest that CTD-induced ROS generation played a critical role in this process, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%